From hermit kingdom to Asian tiger. South Korea's development model (2013)
The Republic of Korea is a particularly striking case within the select group of the four Asian tigers. Despite its previous hostile and adverse conditions for growth, it is currently located within the 15 largest economies on the planet. In this article, we study and analyze the particular political, economic, geographical, demographic and corporate conditions that have guided the country along the path of progress.